Family values between neoliberalism and the new social conservatism - Cooper, Melinda (New York Zone Books, 2017)
"In this book, Melinda Cooper challenges the idea that neoliberalism privileges atomized individualism over familial solidarities, and contractual freedom over inherited status. Delving into the history of the American poor laws, she shows how the liberal ethos of personal responsibility was always undergirded by a wider imperative of family responsibility and how this investment in kinship obligations is recurrently facilitated the working relationship between free-market liberals and social conservatives"--Provided by publisher.
Keywords: Families; Values; Neoliberalism; Conservatism